MELEMAHNYA INTERNALISASI NILAI KARAKTER LOKAL DALAM PENDIDIKAN DI TENGAH ARUS GLOBALISASI BUDAYA - Nabil Aisar Abra; Abdullah Ali (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character building is a fundamental aspect of education; however, its implementation still faces various challenges, particularly in the context of cultural globalization. Normative and insufficiently contextualized character education makes character values difficult to internalize in students’ behavior. This article aims to examine the implementation of character building based on local wisdom and the factors that influence its success in shaping students’ attitudes and behaviors. This study employs a qualitative approach using the library research method. Data were collected by analyzing various literature sources, such as journal articles, books, and the results of previous studies related to the object of study. The findings indicate that the integration of local wisdom values into learning processes and school culture can strengthen students’ character formation in a contextual and sustainable manner. The success of the implementation is influenced by educators’ commitment, exemplary conduct, and support from the school environment and the community. These findings emphasize the importance of local wisdom as a strategic foundation in character education.